Early Modern Asceticism : Literature, Religion, and Austerity in the English Renaissance - McGrath, Patrick J., 1984- (Book collections on Project MUSE., 2020)
"In discussions of the works of Donne, Milton, Marvell, and Bunyan, Early Modern Asceticism shows how conflicting approaches to asceticism animate depictions of sexuality, subjectivity, and embodiment in early modern literature and religion. The book challenges the perception that the Renaissance marks a decisive shift in attitudes towards the body, sex, and the self. In early modernity, self-respect was a Satanic impulse that had to be annihilated--the body was not celebrated, but beaten into subjection--and, feeling circumscribed by sexual desire, ascetics found relief in pain, solitude, and deformity. On the basis of this austerity, Early Modern Asceticism questions the ease with which scholarship often elides the early and the modern."--